Legal Protection for Land Buyers whose Sale and Purchase Deeds are Not Registered at the Land Office - Prakoso, Chrisdrianto Aji; Adonara, Firman Floranta; Effendi, A'an (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The approach to buying and selling land rights that is most often used by PPAT has problems, especially the trading of land rights related to sales and purchases that have been completed with a sale and purchase deed, but the sale and purchase deed does not immediately appear again. for registration at the Land Association Office. This results in uncertainty regarding the position of land objects, so that problems arise for land buyers to seek legal protection and find ways to resolve this. The research focus in this thesis is: First, finding legal certainty for land buyers whose sale and purchase deeds are not registered at the land office. Second, exploring efforts to identify questions if there are land sellers and buyers whose sale and purchase deeds are not registered at the land office. This exploration regulates juridical examination. The methodology used is a legal methodology, which is used to analyze legal guidelines relating to halal guarantees for land buyers whose sale and purchase deeds are not registered at the land office; The conceptual approach used to examine the legal certainty regarding buyers of land whose sale and purchase is not considered in the legal office, as well as the case approach for establishing legal restrictions in order to investigate the legal issues in this research. The results of the first thesis research, legal certainty regarding land buyers whose sale and purchase deeds are not registered with the land office is not valid according to law, because the buyer who carries out the sale and purchase does not become the owner until his position is large enough as long as he is proven to be the owner in the case of an exchange of privileges to him. the territory has been registered at the Land Office. Secondly, the effort to resolve disputes between sellers and buyers of land whose sale and purchase deeds have not been registered at the land office is, to obtain legal certainty, the buyer requests validation by making a lawsuit to the District Court, so that this agreement can then be used as reason for registering the exchange of land rights with the nearest Land Office, thereby providing legal certainty to the injured party as the land owner. The process, then the parties make a deed of sale and purchase to PPAT based on proof of sale and purchase receipts and the results of the ratification decision from the District Court to also be used as a condition for registering the exchange of land rights based on the will from the seller to the buyer, and in the future there is a need for legal reform prospects. to handle the problem. Considering the consequences of this inspection, there are several ideas given, specifically: First, it is necessary to add new rules or articles in PP Number 18 of 2021 which regulate the maintenance and updating of data after land registration, because in PP Number 18 of 2021 it only explains the meaning of Land Registration only in the General Definition in point number 9. Second, there needs to be increased preventive action that must be carried out by the PPAT before accepting applications for making land deeds by the parties, by applying precision and accuracy in reading the files submitted by the parties. The buyer is advised to be more careful, careful and understand more about the procedures for buying and selling land as stipulated in Government Regulation Number 18 of 2021 and to immediately change the name or register the rights at the local land office. This is so that land disputes do not occur in the future and it is detrimental for the buyer to obtain legal certainty.